Drug Resistant Hypertension - No SIMPLE Way Out - Janusz Skrzypecki; Marcin Ufnal (Karger Publishers, 2015)
Hypertension poses growing challenge for health policy-makers and doctors worldwide. Recently published results of Symplicity-III trial (HTN-3), the first blinded, randomized, multicenter study on the efficacy of renal denervation for the treatment of resistant hypertension did not show a significant reduction of BP in patients with resistant hypertension 6 months after renal-artery denervation, as compared with controls. In this paper we review clinical and experimental studies on renal denervation. In order to identify causes of inconsistent results in renal denervation studies we look at basic science support for renal denervation and at designs of clinical trials.